2020
DOI: 10.1177/1971400920910644
|View full text |Cite
|
Sign up to set email alerts
|

Coiling for a saccular aneurysm on the caudal channel in double origin of the posterior inferior cerebellar artery

Abstract: Background Double origin of the posterior inferior cerebellar artery (DOPICA) is a rare cranial imaging finding with an incidence of 0.36–6% reported in various retrospective studies. Aneurysms on a DOPICA are even rarer. Case description A 34-year-old women hospitalised for subarachnoid haemorrhage showed a ruptured aneurysm arising from the caudal channel of the DOPICA. Endovascular treatment was selected, and the aneurysm was successfully and completely embolised using two coils. Conclusions To date, a tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Interestingly, most of the previous literature reported a DOPICA associated with intracranial aneurysms, especially with vertebral and PICA dissecting aneurysms [1, 7, 8, 12-15], while only 2 cases described an associated saccular aneurysm [16, 17]. The endovascular treatment of these aneurysms associated with a DOPICA has also been reported previously [1, 7, 8, 12, 14, 16-18].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Interestingly, most of the previous literature reported a DOPICA associated with intracranial aneurysms, especially with vertebral and PICA dissecting aneurysms [1, 7, 8, 12-15], while only 2 cases described an associated saccular aneurysm [16, 17]. The endovascular treatment of these aneurysms associated with a DOPICA has also been reported previously [1, 7, 8, 12, 14, 16-18].…”
Section: Discussionmentioning
confidence: 80%
“…However, no previous studies reported the presence of this anatomical variation associated with a ruptured AVM in a pediatric patient. The literature reports that navigation through DOPICA channels has been performed previously to treat aneurysms [1, 8, 16, 17], and NBCA was used in 1 case to obliterate a ruptured aneurysm and the parent artery [1]. Moreover, surgical nuances have been reported to perform a correct clipping when a DOPICA was present [13, 15, 19].…”
Section: Discussionmentioning
confidence: 99%